2011
DOI: 10.3109/17477166.2010.490268
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype analysis of the apolipoprotein A5 gene in obese pediatric patients

Abstract: While previous studies in adults demonstrated, that the APOA5 -1131C minor allele confers risk for adult metabolic syndrome, here we show, that the susceptibility nature of this SNP restricted to the APOA5*2 haplotype in pediatric obese subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 45 publications
(56 reference statements)
1
18
0
Order By: Relevance
“…In consistent with our results, Horvatovich et al revealed that APOA5 *2 haplotype (containing the minor alleles of rs662799, rs2072560 and rs2266788) confers susceptibility to development of obesity in pediatric patients [13]. Additionally, in Aberle’s study, at baseline, TT homozygotes had a lower BMI compared to carriers of the C allele, although without a statistical significance [14].…”
Section: Discussionsupporting
confidence: 91%
“…In consistent with our results, Horvatovich et al revealed that APOA5 *2 haplotype (containing the minor alleles of rs662799, rs2072560 and rs2266788) confers susceptibility to development of obesity in pediatric patients [13]. Additionally, in Aberle’s study, at baseline, TT homozygotes had a lower BMI compared to carriers of the C allele, although without a statistical significance [14].…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to the −1131T>C (rs662799) variant the c533G>T variants or T1259C allele had lower BMI and reduced risk to obesity [52, 53]. The Brazilian elderly longitudinal study identified that the GC haplotype of polymorphisms in ApoA1 (rs12721026) and ApoA5 (rs1729408) were associated with high risk to obesity [54].…”
Section: Apoa5 In Cardiometabolic Diseasesmentioning
confidence: 99%
“…In another haplotype study [40], the major haplotype represented an independent protective effect against development of metabolic syndrome [31]. Tagging SNPs and the major haplotype profiles were compared in pediatric obese children with normal controls.…”
Section: Common Polymorphisms and Haplotypes Of Apoa5mentioning
confidence: 99%